2003
DOI: 10.1002/app.12454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monomethyl itaconate‐grafted HDPE and EPR on the compatibility and properties of HDPE–EPR blends

Abstract: ABSTRACT:To improve the compatibility and properties of blends based on high-density polyethylene (HDPE) and the ethylene-propylene copolymer (EPR), the functionalization of both through grafting with an itaconic acid derivative, monomethyl itaconate (MMI), was investigated. The grafting reaction was performed at 180°C in a Brabender Plasticorder using an initial monomer concentration of 3 phr in the case of HDPE and 5 phr in the case of EPR. 2,5-Dimethyl-2,5-bis(tert-butylperoxy)hexane was used as a radical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…In case of CO 2 H-PMS, the success of the hydrosilylation reaction was confirmed by appearance of new absorption band at 1741 cm À 1 assigned to the stretching vibration of ester carbonyl group of the MMI linked to PMS. This absorption band appears at 1744 cm À 1 when MMI was grafted onto high-density polyethylene [90]. Furthermore, absorption bands at 1264 and 808 cm À 1 confirmed the presence of the Si-CH 3 bond.…”
Section: Resultssupporting
confidence: 60%
“…In case of CO 2 H-PMS, the success of the hydrosilylation reaction was confirmed by appearance of new absorption band at 1741 cm À 1 assigned to the stretching vibration of ester carbonyl group of the MMI linked to PMS. This absorption band appears at 1744 cm À 1 when MMI was grafted onto high-density polyethylene [90]. Furthermore, absorption bands at 1264 and 808 cm À 1 confirmed the presence of the Si-CH 3 bond.…”
Section: Resultssupporting
confidence: 60%
“…Our previous work has shown that PP grafted with MMI has better performance in promoting interfacial adhesion between polymers with different polarities. 13 Moreover, MMI its less toxic than MA. Therefore, the use of functionalized PP, either with MA or MMI, facilitate the interaction with CHI.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the similarity of the chemical structure between polymers and compatibilizer is very important to have good enhancement in the final properties of the blends. In our research group, after having studied blends of PP with EPR,30 PE with EPR31 and PP with PET,32 we thought that the use of binary compatibilizer systems with similar structures as those of polymeric wastes would help to improve the compatibility and hence the mechanical properties of the blends. In this work, we report the use of SEBS/EPR and SBR/EPR as compatibilizers to obtain PE/PP/PS, PE/PP/HIPS and PE/PP/PS/HIPS blends.…”
Section: Introductionmentioning
confidence: 99%